URGENSI PENDIDIKAN AGAMA ISLAM DALAM MENYIKAPI DIGITALISASI - Hanifa Naufa Putri (CV. Denasya Smart Publisher, 2025)
In the midst of rapid digitalization and technological advancement, the urgency of Islamic Religious Education (PAI) in shaping students’ character and morality is becoming increasingly evident. While digitalization offers positive contributions to the field of education, it also presents serious challenges such as cyberbullying, exposure to negative content, and a moral identity crisis among adolescents. This study aims to explore the strategic role of PAI in addressing these challenges through a literature review approach by analyzing relevant academic sources and curriculum documents. The findings indicate that PAI plays a vital role not only in delivering religious knowledge but also in shaping students’ spiritual character and digital ethics. Religious education teachers act as value agents who guide students to apply Islamic teachings within their digital lives. Therefore, there is a pressing need to strengthen the curriculum and develop learning methods that integrate Islamic values with digital literacy. With the right and innovative approach, PAI can serve as an effective moral foundation in nurturing a generation of Muslims who are religious, digitally literate, and wise in navigating the dynamics of the digital world. The role of PAI is crucial in fostering a generation that is able to respond to the digital era with strong character and firmly rooted Islamic values.